Characterization of cotton fabric reinforced geopolymer composites modified with Portland cement - Alomayri, T.; Ahmed, Shaikh; Low, It Meng (John Wiley & Sons, Inc., 2013)
Fly-ash based geopolymer composites reinforced with cotton fabric (CF) and containing Ordinary Portland cement (OPC) have been fabricated and investigated in terms of x-ray diffraction, scanning electron microscopy and mechanical properties. Results indicated that the mechanical properties of geopolymers generally increased as a result of OPC addition. The addition of OPC also enhanced the fibre-matrix adhesion and led to geopolymer composites with improved strength because of the formation of calcium silicate hydrate (C-S-H) gel which filled the voids and pores within the matrix. However, SEM images of fracture surfaces revealed that OPC addition hindered the toughening mechanism by limiting the prevalence of fibre pull out. As the OPC content increases, the density of geopolymer composites increases by virtue of a reduction in porosity via the formation of C-S-H gels.